Use of Electronic Information Services in Research Libraries - Sami, Lalitha K.; Iffat, Rabia (Journal of Information and Knowledge, 2013)
The paper discusses the use of Electronic Information Services (EIS) introduced in the research libraries. The paper further analyses whether the awareness about the services and the background of the users have any impact on the use of Electronic Information Services.